TIME OF CHANGES: THE PATH TO "RECOVERY" ENVIRONMENT AND YOUTH POLICY FOR YOUNG PEOPLE - Когiakovtseva, Olga; Upeniece, Irena; Dosse, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The Article is devoted to problems of improvement of the youth environment in conditions of social transformations. The authors examine the role of youth policy of the state and society in solution of the mentioned problems. The article suggests a system of measures for the development of spiritual, moral, cultural and physical potential of young people. Based on subject-subject approach is determined by the conditions of their realization. Confirmation of the authors ' conclusions are results of research of processes of socialization, participation and samuoliene youth in society, the motives and peculiarities of manifestation of its civic consciousness, value scale of young people.